Órganos vitales y metáforas mortales: un relato sobre hospitales portugueses y diáspora africana - Sarró, Ramon (Revista de Antropología Social, 2007)
This article, based on a case of medical neglect towards an African migrant, explores rumours about organ theft in Portuguese hospitals spread among African migrants. The author sees these rumours as an expression of rage against a society that marginalizes and excludes migrants. Contrariwise to authors who have studied organ theft rumours as an expression of “millennial capitalism”, he proposes to centre the attention in the continuities rather than in abrupt ruptures. The author takes some distance from scholars for whom the investigation on rumours would only make sense inasmuch as it could lead towards denouncing specific real cases. For the author, rumours themselves can lead us towards other injustices, much more embedded in our everyday life, that must also be denounced.